A Methodology for the Evaluation of the Economic Impacts of Wind Energy Projects. Issue 5 (September 2013) - Landry, Mathieu A.; Leclerc, André; Gagnon, Yves
In this paper, a methodology for the evaluation of the economic impacts of wind energy projects is presented. With an application to the Canadian setting, the methodology is based on modified input-output techniques using national/provincial economic Input-Output tables and multiplier coefficients. The model makes use of a profile of investment for a generic 100 MW wind energy project based on publicly available financial data from current wind energy projects developed and operating in Canada. Subsequently, a case study of the economic impact assessment for both the construction and operations phases of a generic 100 MW wind farm project constructed and operated in the province of New Brunswick, Canada is performed. Results show that in total, including direct, indirect and induced jobs, the construction phase could create a total of 225 person-years of labour, while the operations and maintenance phase could create a total of 17 person-years of labour annually.